Exploring the association of mindfulness, confidence, competitive state anxiety, and attention control in soccer penalty shootouts - Shi, Lisi; Jing, Longjun; Wang, Huilin; Liu, Yang (Frontiers in Psychology, 2024)
Introduction: Penalty shootouts are a pivotal factor influencing outcomes in soccer matches. Soccer players face the challenge of overcoming physical fatigue and psychological pressure when taking penalty kicks. Instances of low confidence and competitive state anxiety during matches exacerbate the detrimental impact on attention control, particularly in non-target defined features, leading to suboptimal performance during penalty kicks.This cross-sectional survey investigates the relationship between mindfulness and attention control. Convenient sampling was employed to gather a sample of 266 soccer players from sports teams and training bases in Central and South China who had participated in city-level or higher-level competitions. A structural equation model, created using AMOS 26, was employed for hypotheses validation.Results: Findings reveal a positive correlation between mindfulness and confidence, and a negative correlation between mindfulness and competitive state anxiety. Additionally, confidence positively associates with attention control, while competitive state anxiety shows a negative relationship with attention control. Confidence and competitive state anxiety also function as mediators in the correlation between mindfulness and attention control. To elaborate, soccer penalty kickers with heightened mindfulness demonstrate increased confidence levels, reduced competitive state anxiety, and improved attention control.: Mindfulness training positively influences attention control during penalty kicks for soccer players. To boost players' confidence, alleviate competitive state anxiety, and enhance their performance during penalty shootouts, it is recommended that governments increase investment in mindfulness training and talent development. Coaches should enhance their understanding of mindfulness training mechanisms, and athletes themselves should prioritize mindfulness training.